Efeitos da dosagem de monensina sódica sobre o desempenho produtivo, comportamento ingestivo, saúde ruminal e características de carcaça em bovinos Nelore confinados - Pereira, Murillo Ceola Stefano [UNESP] (2014)
The experiment was designed to determine the effects of different doses of sodium monensin on feedlot performance, feeding behavior, ruminal health and carcass carcass characteristics of Nellore cattle. The experiment was designed as a completely randomized block, replicated 12 times, in which 60 20-months old yearling Nellore bulls (402.52 ± 33.02 kg) were fed in individual pens for 84 days according to the different doses of monensin expressed in ppm (dry matter basis): 0, 9, 18, 27 and 36. The adaptation program consisted of ad libitum feeding of two adaptation diets over period of 14 days with concentrate level increasing from 68% to 84% of diet dry matter. Polynomial contrasts were used to assess linear, quadratic, cubic and quartic relationship between doses of MON and the dependent variable. As dose of monensin improved final body weight, average daily gain, gain to feed ratio, net energy for gain, absorptive surface (P < 0.05) affected cubically and mitotic index (P < 0.10) affected quadratically. The dry matter intake decreased linearly (P < 0.01). As doses of MON increased, hot carcass weight decreased (P < 0.01) affected linearly. Dressing percentage was affected cubically (P = 0.03), as dose of MON increased. Thus, based on the results of this study, increasing doses of MON affected feedlot performance, ingestive behaviour, ruminal health and carcass characteristics of Nellore cattle. If MON is going to be included in finishing diets for feedlot Nellore cattle, the dose of 9 ppm should be considered as the most feasible option